2014
DOI: 10.4082/kjfm.2014.35.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hepatitis B Surface Antigen Seropositivity and Metabolic Syndrome

Abstract: BackgroundInfection with hepatitis B virus (HBV) may be a risk factor for cardiovascular disease. We investigated the relationship between HBV infection and metabolic syndrome.MethodsWe performed a cross-sectional study of 9,474 Korean men and women who were at least 20 years old and who underwent a routine health check-up at Ulsan University Hospital in Ulsan, South Korea between March 2008 and February 2009. The associations of hepatitis B surface antigen (HBsAg) seropositivity with the presence of metabolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 25 publications
4
26
3
Order By: Relevance
“…Using structural equation modeling, we found a direct favorable effect of chronic HBV infection on lipid profiles, but no significant effect on other metabolic derangements in both the males and females after taking into account potential confounders and interactions. Previous studies have also shown an inverse association between chronic HBV infection and triglyceride levels in different ethnic populations . Similarly, we found that chronic HBV infection was associated with a lower prevalence of hypertriglyceridemia among nondiabetic subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Using structural equation modeling, we found a direct favorable effect of chronic HBV infection on lipid profiles, but no significant effect on other metabolic derangements in both the males and females after taking into account potential confounders and interactions. Previous studies have also shown an inverse association between chronic HBV infection and triglyceride levels in different ethnic populations . Similarly, we found that chronic HBV infection was associated with a lower prevalence of hypertriglyceridemia among nondiabetic subjects.…”
Section: Discussionsupporting
confidence: 86%
“…Chronic HBV infection is associated with lower prevalence of hypertriglyceridemia in men and women (Jan et al 2006;Chen et al 2010;Wong et al 2012;Chung et al 2014;Huang et al 2016). In this study, however, OBI was detected at higher frequency in HLP patients than in replacement blood donor population controls (9.5% vs. 2.4%, P < 0.001), which suggested a positive association between OBI and HLP.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies showed that chronic hepatitis B virus (HBV) infection was associated with lower prevalence of hypertriglyceridemia (Jan et al 2006;Chen et al 2010;Wong et al 2012;Chung et al 2014;Huang et al 2016) or hypercholesterolemia (Chen et al 2010;Liu et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, no possible gender effect of CHB on MS was examined, despite adjustment for age and gender. Consistent with us, Chung et al explored how gender differences affected the association between the MS and CHB infection and showed that HB infection was negatively associated with MS in men [Chung et al, ]. Zhou et al in a 20‐year follow‐up retrospective cohort study in Shanghai, showed a positive association between HB infection and MS [Zhou et al, ].…”
Section: Discussionmentioning
confidence: 74%